Effects of Behavioral Activation on the Quality of Life and Emotional State of Lung Cancer and Breast Cancer Patients During Chemotherapy Treatment. Issue 2 (March 2019) - Fernández-Rodríguez, Concepción; Villoria-Fernández, Erica; Fernández-García, Paula; González-Fernández, Sonia; Pérez-Álvarez, Marino
Research suggests that the progressive abandonment of activities in cancer patients are related to depression and worse quality of life. Behavioral activation (BA) encourages subjects to activate their sources of reinforcement and modify the avoidance responses. This study assesses the effectiveness of BA in improving quality of life and preventing emotional disorders during chemotherapy treatment. One sample of lung cancer patients and another of breast cancer patients were randomized into a BA experimental group (E.G.lung/4sess . n = 50; E.G.breast/6sess . n = 33) and a control group (C.G.lung/4sess . n = 40; C.G.breast/6sess. n = 35), respectively. In each session and in follow-ups (3/6/9 months), all participants completed different assessment scales. The results converge to show the effectiveness of BA, encouraging cancer patients to maintain rewarding activities which can activate their sources of day-to-day reinforcement and modify their experience avoidance patterns. BA appears to be a practical intervention which may improve social and role functioning and the emotional state of cancer patients during chemotherapy treatment.